Comparison of regeneration of bone produced from the adipose tissue stem cells with autogenous bone: an animal study - Nakisa Torabinia; Batol Hashemibani; Naser Pour Ebrahim; Shirin Shahnaseri (Isfahan University of Medical Sciences, 2011)
Introduction: This study compared bone produced by tissue engineering from the adipose tissue stem cells with autogenous bone graft (ABG) in the repair of alveolar cleft model in the maxilla of dogs. Materials and Methods: In this experimental-interventional study, mesenchymal stem cells were isolated from four dog's subcutaneous fat tissue after detecting the markers by flow cytometry; then the cells were proliferated after cultivation. These cells were cultured in hydroxyapatite tricalcium phosphate scaffolds and placed in a special osteogenic environment. Accuracy of mesenchymal stem cell osteogenic induction was confirmed by RT-PCR. At first in 4 dogs, two teeth of the three incisors were removed on each side and a 15-mm-wide defect was produced on both sides from the alveolar crest to the nasal cavity floor. Nasal mucosa was sutured to the oral mucosa. To preserve the space, a stent was placed on each side. After 60 days, on one side the cleft was regenerated with osteogenic cells produced from osteogenic differentiation and with the autogenous bone obtained from dog's tibia on the other. Bone regeneration was assessed at 15- and 60-day intervals post-operatively with biopsy by histomorphometry. Data was analyzed with descriptive statistical tests and t-test (α = 0.05). Results: Mean bone regeneration at 15- and 60-day intervals on the autograft and the stem cell sides were 45%, 95%, 5% and 70%, respectively. Statistical analysis revealed significant differences in bone formation between the two autograft and stem cell groups at both intervals (p values of 0.004 and 0.001, respectively). Conclusion: Tissue engineering can be used as an alternative technique with clinical success and optimal bone formation in cases with limited access to autogenous bone or with possibility of significant morbidity at the site. Key words: Alveolus, Cleft, Stem cells, HAP-TCP.